Why am I not your perfect family member? Casual attribution moderates the impacts of relational self-discrepancy - Xiong, Rui (Nanyang Technological University, 2022)
Relational self-discrepancy occurs when there is a mismatch between individuals’ self-representations of who they are in the eyes of their important others and who their important others expect them to be. Self-Discrepancy Theory predicts relational self-discrepancy to be associated with various negative emotions, but the predicted associations are not always empirically supported. To explain the inconsistencies, this study integrates Self-Discrepancy Theory and Attribution Theory to examine whether causal attribution moderates the discrepancy-emotion links. Furthermore, this study expands Self-Discrepancy Theory by investigating the effects of relational self-discrepancy on relational functioning mediated by specific negative emotions. We recruited 159 undergraduates in Singapore to participate in an online survey about their relational self-discrepancy from their families’ perspectives. Our regression analyses show that relational self-discrepancy is positively associated with guilt and anger, but its association with guilt only applies to individuals with a high (vs low) tendency to attribute the discrepancy to causes within their own control. Relational self-discrepancy is negatively associated with relational functioning and this association is partially mediated by guilt and anger, both of which are negatively associated with relational functioning. However, the indirect effect of relational self-discrepancy on relational functioning via guilt only applies to individuals with a high (vs low) tendency to attribute the discrepancy to causes within their own control. Implications and limitations are discussed.